2017
DOI: 10.1186/s12885-017-3864-6
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma cells replicate through chemotherapy by reducing levels of key homologous recombination protein RAD51 and increasing expression of translesion synthesis DNA polymerase ζ

Abstract: BackgroundThe global incidence of melanoma has been increasing faster than any other form of cancer. New therapies offer exciting prospects for improved survival, but the development of resistance is a major problem and there remains a need for additional effective melanoma therapy. Platinum compounds, such as cisplatin, are the most effective chemotherapeutics for a number of major cancers, but are ineffective on metastatic melanoma. They cause monofunctional adducts and intrastrand crosslinks that are repair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
(48 reference statements)
1
7
0
Order By: Relevance
“…In addition, in line with previous reports we observed that enforced miR-204-5p expression was also able to inhibit the expression levels of RAD51, FOXM1 and NOTCH1 [18] (Supplementary Fig. S3B) [2527]. Moreover, MAPKi-resistant melanoma cells consistently underwent a prominent increase of endogenous NOTCH1 levels and a cell-type dependent increase of the other two miR-204-5p targets RAD51 and FOXM1 (Supplementary Fig.…”
Section: Resultssupporting
confidence: 89%
“…In addition, in line with previous reports we observed that enforced miR-204-5p expression was also able to inhibit the expression levels of RAD51, FOXM1 and NOTCH1 [18] (Supplementary Fig. S3B) [2527]. Moreover, MAPKi-resistant melanoma cells consistently underwent a prominent increase of endogenous NOTCH1 levels and a cell-type dependent increase of the other two miR-204-5p targets RAD51 and FOXM1 (Supplementary Fig.…”
Section: Resultssupporting
confidence: 89%
“…Our earlier result showed that the IC 50 value of cisplatin treatment was reduced by ~ 2 fold with ACPH in A375 cells [5]. Olaparib, another PARP1 inhibitor decreased the IC 50 value of cisplatin by ~ 5 fold in A375 cells [35]. For combined treatment with cisplatin and 4NCO in A375 cells, the fold reduction IC 50 was found to be ~ 12 fold at some concentrations chosen for the study, which indicated that 4NCO was much more productive in potentiating the sensitivity to cisplatin-induced killing.…”
Section: Discussionmentioning
confidence: 99%
“…10,43,44 Interestingly, we noticed that although combined treatment with JQ1 and HDACIs robustly abolished the expression of endogenous RAD51, the expression of exogenous HA-RAD51 (under a CMV promoter) was essentially unaffected. RAD51 expression can be regulated via transcription, miRNAs including miR-96, −99, −107, −222 and −155, and protein stability, 45 further studies are warranted to disclose the detailed regulatory mechanism of JQ1 combined with HDACIs in regulating RAD51 expression in chondrosarcoma.…”
Section: Discussionmentioning
confidence: 99%